Conductivity Study of DTAB in Water and Ethanol-Water Mixture in the Presence and Absence of ZnSO4 (Baghdad Science Journal, 2020)
The physicochemical behaviour of dodecyltrimethylammonium bromide (DTAB) in water and ethanol-water mixture in the presence and absence of ZnSO4 were studied by measuring the conductivity at 298.15 K. The pre-micellar (S1) and post-micellar slopes (S2) were obtained and calculated the degree of dissociation (α) and the critical micelle concentration (cmc). With an increase in ethanol content, the cmc and α of DTAB increased whereas, in the presence of ZnSO4, the cmc and α decreased. By using cmc and α, thermodynamic properties as the standard free energy of micellization ( ) were evaluated. With an increase in ethanol content, the negative values of are decreased indicating less spontaneous in the micellization which makes micellization less favourable. The correlation of the pre-micellar and post-micellar slopes with the volume fraction of ethanol were discussed. DTAB micellization was tested in contexts of specific solvent parameters and solvophobic parameter.